Dalhuisen on transnational and comparative commercial, financial and trade law. Volume 5, Financial products and services - Dalhuisen, J. H. (Jan Hendrik) (London [England] : Hart Publishing, 2022)
"... presents a very different case: that of a civilized and cultivated cosmopolitan legal scholar, with a keen sense of international commercial and financial practice, with an in-depth grounding in both comparative legal history and comparative law, combined with the ability to transcend conventional English black-letter law description with critical judgment towards institutional wisdom and intellectual fashions." ( International and Comparative Law Quarterly ) Volume 5 of this new edition uses the insights developed in Volumes 3 and 4 to deal with financial products and financial services, the structure and operation of banking and of the capital markets, and the role of modern commercial and investment banks. Sections on products and services address the blockchain and its potential in the payment system, in securitisations, in the custodial holdings of investment securities, and in the derivative markets. The complete set in this magisterial work is made up of 6 volumes. Used independently, each volume allows the reader to delve into a particular topic. Alternatively, all volumes can be read together for a comprehensive overview of transnational comparative commercial, financial and trade law."--
1. Secured Transactions, Finance Sales and Other Financial Products and Services 1.1 Civil and Common Law Approaches to Financial Law. Credit Cultures and Transnationalisation 1.2 The Situation in the Netherlands 1.3 The Situation in France 1.4 The Situation in Germany 1.5 The Situation in the UK 1.6 The Situation in the US -- 2. Financial Products and Funding Techniques. Private, Regulatory and International Aspects 2.1 Finance Sales as Distinguished from Secured Transactions: The Re-characterisation Risk 2.2 Modern Security Interests: The Example of the Floating Charge 2.3 Receivable Financing and Factoring. The 1988 UNIDROIT Factoring Convention and the 2001 UNCITRAL Convention on the Assignment of Receivables in International Trade 2.4 Modern Finance Sales: The Example of the Finance Lease. The 1988 UNIDROIT Leasing Convention 2.5 Asset Securitisation and Credit Derivatives. Covered Bonds 2.6 Options, Futures and Swaps. Their Use and Transfers. The Operation of Derivatives Markets, Clearing and Settlement and the Function of Central Counterparties 2.7 Institutional Investment Management, Funds, Fund Management and Prime Brokerage -- 3. Payments, Modern Payment Methods and Systems. Set-off and Netting as Ways of Payment. International Payments. Money Laundering 3.1 Payments, Payment Systems. Money and Bank Accounts 3.2 The Principles and Importance of Set-off and Netting 3.3 Traditional Forms of International Payment 3.4 Money Laundering -- 4. Security Entitlements and Their Transfers through Securities Accounts. Securities Repos 4.1 Investment Securities Entitlements and Their Transfers. Securities Shorting, Borrowing and Repledging. Clearing and Settlement of Investment Securities 4.2 Investment Securities Repos
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Financial services industry -- Law and legislation; Commercial law; Electronic books